The MYH9 Cytoskeletal Protein Is a Novel Corepressor of Androgen Receptors - Liu, Chunhua; Liao, Zhaoping; Duan, Xiuzhi; Yu, Pan; Kong, Piaoping; Tao, Zhihua; Liu, Weiwei (Frontiers in Oncology, 2021)
In the progression of castration-resistant prostate cancer (CRPC), the most remarkable molecule is the androgen receptor (AR), a protein that binds to androgens and acts as a transcription factor. The transcriptional activity of AR is regulated by coregulators. As a result, altered expression levels, an aberrant location or activities of coregulators contribute to the progression of prostate cancer. We describe herein results showing that AR nuclear translocation capability is enhanced in androgen-independent prostate cancer (AIPC) cells compared to androgen-dependent prostate cancer (ADPC) cells. To gain insight into whether AR coregulators are responsible for AR translocation capability, we performed coimmunoprecipitation (CO-IP) coupled with LC-MS/MS to screen 27 previously reported AR cofactors and 46 candidate AR cofactors. Furthermore, one candidate, myosin heavy chain 9 (MYH9), was identified and verified as a novel AR cofactor. Interestingly, MYH9 was primarily distributed in both the cytoplasmic and nuclear compartments but was concentrated in the nucleus after AR was knocked down by AR shRNA, suggesting that the nuclear translocation of MYH9 was negatively regulated by AR. In addition, we found that blebbistatin, an inhibitor of MYH9, not only promoted AR nuclear translocation but also increased the expression of the AR target gene PSA, which indicates that MYH9 represses AR signaling. Taken together, our findings reveal that MYH9 appears to be a novel corepressor of AR involved in the progression of CRPC.